Bank risk-taking and legal origin: What do we know about dual banking economies? - Mohsin Ali; Nafis Alam; Mudeer Ahmed Khattak; Wajahat Azmi (Journal of Risk and Financial Management, 2022)
This paper investigates the relationship between legal origin and banks' risk-taking behavior. We employ GMM to study a sample of both Islamic and conventional banks from 14 dual banking economies from 2005-2018. Our findings can be summarized as follows: (a) bank risk-taking and legal origin are negatively related in our sample countries, (b) Islamic banks are more stable in English law (common) countries, and (c) bank regulations have a differential effect on Islamic and the conventional banks. Our overall findings align with the dark side of the legal framework, indicating a robust legal framework to encourage bank risk-taking. The results have several implications for shareholders, regulators, and other key stakeholders.
Keywords: 650; bank risk-taking; dual banking economies; Islamic banks; legal origin